Shelf life Characteristics of Pangasianodon hypophthalmus Fillets Treated with Moringa oleifera (Lam) Leaf extract - S. S., Greeshma; K., Sarika.; E. R., Priya.; R. G. Kumar, Lekshmi.; Joseph, Toms. C.; Pandey, M. C.; Prasad, M. M. (Fishery Technology, 2019)
Effect of dip treatment in Moringa oleifera (Lam) leaf extract (MOL) on the quality and shelf life of vacuum packed Pangasianodon hypophthalmus fillets was evaluated during chilled storage at 2 Â± 1Â°C. The control (untreated) and treated groups with 5% (v/v) and 10% (v/v) Moringa oleifera leaf extract (MOL) were examined periodically at 0, 3, 6, 9, 12, 15, 18 days during chilled storage until rejection by sensory, physicochemical and microbiological methods. The study revealed that the Moringa oleifera extract is a good source of phenolic compounds with significant antioxidant potential. The total phenolic content was found to be 183.75 mg GAE 100 g-1. MOL was found to have high antioxidant potential. The pH and TBA values of control group were significantly higher (p